A Literature Review on Mantra Meditation - Saini, Ravi; Sorout, Jitender (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Objective: Meditation has gained popularity in modern times as an adjunctive of therapeutic treatment. This study aimed to study meditation and use of mantra meditation in application of health problems. Materials and methods After searching literature through electronic databases, with regards to meditation and mantra meditation in accordance with PRISMA method was done. Conclusion: Meditation does not deal only spiritual aspect but it has various application as complimentary in various health related problems.